Assessment of knowledge of women about laparoscopic and hysteroscopic operations in Gynecology in Kerbala city - Alsafi, Wasan Ghazi (Karbala Journal of Medicine, 2019)
Abstract Endoscopic operations in gynecology nowadays have major role in resolving many problems. There are certain preparations preoperatively for these operations and certain complications may happen. The current study aimed to estimate the knowledge about these preoperative preparation and complications in laparoscopy and hysteroscopy in women attending for having such operation. One of the best ways to avoid complications is to recognize those situations in which they are most likely to occur. Patients and methods: A cross sectional study was conducted on forty women given dating for hysteroscopic and laparoscopic operations at the Al- Kafeel superspeciality hospital in holy Karbala city for the period from 1-3-2017 to 1-9-2017 a questionnaire was given for every woman, data was collected and analyzed to know the level of health awareness among them about these operations. Results: In this study we found that, all the patients know the need to take drugs after surgery about (100 %), The percent of them who know to empty bladder and intestine before operation of the rate (70 %). The Large percent of women knows about preoperative investigations before operations of the rate (90 %), all the woman know about the need for anesthesia for the intervention about (100 %). Also there are different ranges of them know about the benefit from doing these endoscopic operations. Regarding knowledge about complications (57.5 %) of them knows that there is risk of bleeding and Infection after the operations. Conclusion: There is defect in the community in getting enough health issues from social media and staff, so we need to enforce and concentrate on the teaching program in TV, social media and also we should be started in every health center and in even at schools.